Organizational socialization process of MBA graduates - Siti Khadijah Mohd Ghanie; Khairul Akmaliah Adham; Rosmah Mat Isa (Penerbit Universiti Kebangsaan Malaysia, 2018)
Extant literature on organizational socialization has not focused on the relation of education and learning with adjusting to work. As a result, little is known about the contribution of an MBA learning experience towards the process of organizational socialization. The purpose of this study is to understand the organizational socialization process of MBA graduates in their first six months of work. This qualitative study involved interviews with MBA graduates who had been employed within a period of one to six months. This study found that MBA graduates utilized their communication and analytical skills that were enhanced during the MBA education in support of their socialization tactics of relationship building, information gathering and learning. Graduates’ skills and prior experiences were mobilized through the facilitation of immediate superiors and/or supported by mentorship and help by senior co-workers.